Preparation method of perovskite photovoltaic cell
By using a mixed solvent system of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile, the adverse impact of solvent on the environment in the existing perovskite photovoltaic cell preparation methods is solved, and the preparation of high-quality films and the improvement of photovoltaic cell performance is achieved.
Patent Information
- Application Number
- CN202510321780.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
In the existing preparation methods for perovskite photovoltaic cells, solvents used such as N,N-dimethylformamide, N-methylpyrrolidone and ethylene glycol methyl ether have adverse effects on the environment and are difficult to meet performance requirements.
A perovskite precursor solution was prepared using a mixed solvent system of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile, which was fully dissolved by magnetic stirring, and deposited on the hole transport layer through slit coating, and then annealed to form a perovskite light absorbing layer.
Through this method, precursor materials such as PbI2 and MAI can be effectively dissolved, the colloidal solution can be stabilized, the colloidal particle agglomeration can be inhibited, the film stability and consistency can be improved, the solution rheology characteristics can be improved, the coating film formation defects can be avoided, and the film quality and photovoltaic cell performance can be improved.
Smart Images

Figure CN119855459A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a perovskite photovoltaic cell, and relates to the technical field of the perovskite photovoltaic cell. Background Art
[0002] Solution printing has attracted wide attention in the high-throughput production of thin-film semiconductor electronic devices due to its inherent advantages such as simple manufacturing process, low cost and large preparation area. Among them, perovskite materials have become disruptive candidate materials in photovoltaic technology due to their excellent optoelectronic properties. However, lead in perovskite precursors and traditional solvents such as N,N-dimethylformamide, N-methylpyrrolidone and ethylene glycol methyl ether have adverse effects on the environment. Summary of the invention
[0003] In view of this, the present application provides a method for preparing a perovskite photovoltaic cell, establishing a solvent system that is both environmentally friendly and meets performance requirements.
[0004] According to one aspect of the present application, a method for preparing a perovskite photovoltaic cell is provided, wherein the perovskite photovoltaic cell is suitable for being arranged on an external substrate, and comprises the following steps: step one: depositing a transparent conductive substrate on a substrate, wherein the external substrate is a supporting structure of the perovskite photovoltaic cell; step two: preparing a hole transport layer on the transparent conductive substrate; step three: preparing a perovskite precursor solution using a mixed solvent of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile; step four: coating the perovskite precursor solution on the hole transport layer to form a perovskite light absorption layer; step five: depositing an electron transport material on the perovskite light absorption layer to form an electron transport layer; step six: preparing a hole blocking layer on the electron transport layer; step seven: depositing a back electrode on the hole blocking layer.
[0005] According to one aspect of the present application, the volume fraction of the dimethyl sulfoxide is 1% to 20%, the volume fraction of the 2-methyltetrahydrofuran is 70% to 90%, and the volume fraction of the acetonitrile is 1% to 20%.
[0006] According to one aspect of the present application, the volume ratio between the dimethyl sulfoxide, the 2-methyltetrahydrofuran and the acetonitrile is 1:8:1.
[0007] According to one aspect of the present application, the dimethyl sulfoxide, the 2-methyltetrahydrofuran and the acetonitrile are fully dissolved by magnetic stirring to prepare a perovskite precursor.
[0008] According to one aspect of the present application, the perovskite precursor solution is deposited on the hole transport layer by slit coating and annealed at 150° C. for 10 min.
[0009] According to one aspect of the present application, the substrate is a glass substrate, and one of an indium tin oxide film and a fluorine-doped tin oxide film is deposited on the glass substrate to form a transparent conductive substrate; a nickel oxide film is deposited on the conductive substrate by spin coating or magnetron sputtering to form the hole transport layer.
[0010] According to one aspect of the present application, a fullerene layer is deposited on the perovskite active layer by thermal evaporation or spin coating to form the electron transport layer.
[0011] According to one aspect of the present application, a bath copper layer is deposited on the electron transport layer by thermal evaporation or spin coating to form the electron transport layer.
[0012] According to one aspect of the present application, a bath copper layer is deposited on the electron transport layer by thermal evaporation or spin coating to form the hole blocking layer.
[0013] According to one aspect of the present application, a metal electrode is deposited on the hole blocking layer to form the back electrode, and the back electrode is made of silver or copper.
[0014] The beneficial effects of the present invention are as follows: by using dimethyl sulfoxide as the main solvent, its strong polarity and high coordination ability can not only effectively dissolve precursor materials such as PbI2 and MAI, but also 2+ The coordination effect with the S=O group stabilizes the colloidal solution and inhibits the aggregation of colloidal particles. This improves the stability and consistency of the film. 2-Methyltetrahydrofuran is used as a core green solvent. Its low toxicity and high volatility increase the upper limit of the coating rate, promote the rapid volatilization of the solvent, reduce the residual solvent in the film, and accelerate the drying speed. At the same time, its low surface tension significantly improves the rheological properties of the solution, ensuring that the solution spreads evenly on the substrate surface, effectively avoiding coating film defects. Acetonitrile is used as a dynamically controlled solvent. Its high saturated vapor pressure can form a complementary volatilization kinetic curve with 2-methyltetrahydrofuran, achieving the organic unity of high-performance preparation and green manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a structural diagram of a photovoltaic cell with a perovskite thin film according to this embodiment; Figure 2 The donor number and saturated vapor pressure diagram of common perovskite solvents; Figure 3 A comparison diagram of the macroscopic uniformity of perovskite films prepared by the traditional solvent and the solvent system of this embodiment; Figure 4 This is a scanning electron microscope comparison of the perovskite film prepared by high-speed scraping under the traditional solvent and the solvent system of this embodiment; Figure 5 A comparison chart of the thickness uniformity of perovskite films in different solvent systems; Figure 6 Preparation of large-area perovskite components by doctor blade coating in different solvent systems J - V Graphs; Figure 7 This is a diagram illustrating the domestic toxicity of common perovskite solvents. DETAILED DESCRIPTION
[0016] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0017] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0018] like Figures 1 to 7 As shown, the present application provides a method for preparing a perovskite photovoltaic cell, and the perovskite photovoltaic cell is suitable for being arranged on an external substrate, comprising the following steps: Step 1: the substrate serves as a supporting structure of the solar cell, and a transparent conductive substrate ① is deposited thereon; Step 2: a hole transport layer ② is prepared on the transparent conductive substrate ①; Step 3: perovskite materials are prepared and treated, and a perovskite precursor solution is prepared using a mixed solvent system of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile; Step 4: a perovskite precursor material is coated on the hole transport layer ② to form a perovskite light absorption layer ③; Step 5: an electron transport material is deposited on the perovskite light absorption layer ③ to form an electron transport layer; Step 6: a hole blocking layer ⑤ is prepared on the electron transport layer, and finally a back electrode ⑥ is deposited on the hole blocking layer ⑤.
[0019] like Figure 1As shown, the substrate serves as the supporting structure of the perovskite photovoltaic cell, and a transparent conductive substrate ① is deposited thereon as an electrode material for subsequent charge collection and transport. A hole transport layer ② is prepared on the transparent conductive substrate ① to help holes be effectively transported from the perovskite light absorption layer ③ to the electrode. Then the perovskite material is prepared and treated, and a perovskite precursor solution is prepared using a mixed solvent system of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile. The perovskite precursor material is coated on the hole transport layer ② to form a perovskite light absorption layer ③. An electron transport material is deposited on the perovskite light absorption layer ③ to form an electron transport layer ④ to help electrons be transported from the perovskite light absorption layer ③ to the electrode layer, and then a hole blocking layer ⑤ is prepared on the electron transport layer ④ to protect the perovskite light absorption layer ③ and the electron transport layer ④ and promote the efficiency of charge collection. Finally, the back electrode ⑥ is deposited as the top electrode of the entire solar cell, and the prepared perovskite photovoltaic cell is packaged and tested. The packaging can prevent the impact of environmental conditions on the performance of the device, such as changes in light and humidity. The performance of the packaged perovskite photovoltaic cell needs to be tested, including the photoelectric conversion efficiency (PCE), short-circuit current density ( J sc )、Open circuit voltage( V oc ) and fill factor (FF) to evaluate the photoelectric conversion efficiency and stability during the reaction.
[0020] According to one aspect of the present application, the volume fraction of dimethyl sulfoxide is 1% to 20%, the volume fraction of 2-methyltetrahydrofuran is 70% to 90%, and the volume fraction of acetonitrile is 1% to 20%. The volume ratio of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile is 1:8:1. Dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile are fully dissolved by magnetic stirring to obtain a perovskite precursor. The perovskite precursor solution is deposited on the hole transport layer ② by slit coating and annealed at 150°C for 10 minutes.
[0021] The volume ratio of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile is 1:8:1. The perovskite precursor can be obtained by fully dissolving it through magnetic stirring. The precursor is evenly printed on the hole transport layer ② at a speed of 50mm / s using slit coating printing technology, and the distance between the coating head and the substrate is kept at 80μm to form a perovskite film. Subsequently, the wet film is flash evaporated in a vacuum environment (vacuum degree less than 20Pa) for 60s, and then annealed at 150℃ for 10min to complete the entire perovskite film growth process.
[0022] According to one aspect of the present application, the substrate is a glass substrate, and one of an indium tin oxide film and a fluorine-doped tin oxide film is deposited on the glass substrate to form a transparent conductive substrate ①; a nickel oxide film is deposited on the conductive substrate ① by spin coating or magnetron sputtering to form a hole transport layer ②. A fullerene layer is deposited on the perovskite active layer by thermal evaporation or spin coating to form an electron transport layer ④. A bath copper layer is deposited on the electron transport layer ④ by thermal evaporation or spin coating to form an electron transport layer ④. A bath copper layer is deposited on the electron transport layer ④ by thermal evaporation or spin coating to form a hole blocking layer ⑤. A metal electrode is deposited on the hole blocking layer ⑤ to form a back electrode ⑥, and the material of the back electrode ⑥ is silver or copper.
[0023] Preferably, depositing a conductive substrate on a substrate ① further comprises: the substrate is a glass substrate, and an ITO (indium tin oxide) or FTO (fluorine-doped tin oxide) film is deposited on the glass substrate to form a transparent conductive oxide (TCO) coating; preparing a hole transport layer on TCO ② further comprises: depositing NiO on the conductive substrate ① by spin coating or magnetron sputtering x (Nickel Oxide) Thin Film.
[0024] Secondly, preparing the electron transport layer ④ on the perovskite light absorption layer ③ also includes: depositing fullerene (C 60 or PCBM) layer, which is used as an electron transport material to help electrons transfer from the perovskite light absorption layer ③ to the electrode layer.
[0025] Then, preparing the hole blocking layer ⑤ on the electron transport layer ④ also includes: depositing a bath cuproline (BCP) layer on the electron transport layer ④ by thermal evaporation or spin coating to protect the perovskite light absorption layer ③ and the electron transport layer ④ and promote charge collection efficiency.
[0026] Finally, preparing a back electrode ⑥ on the hole blocking layer ⑤ and packaging the photovoltaic cell with the perovskite film also includes: depositing a metal electrode on the hole blocking layer ⑤ to complete the preparation of the photovoltaic cell with the perovskite film, packaging the prepared solar cell, and performing performance testing on the packaged photovoltaic cell with the perovskite film.
[0027] In this embodiment, a metal electrode is deposited on the BCP layer as the top electrode of the entire photovoltaic cell with a perovskite film, wherein the metal electrode is silver or copper. The finished photovoltaic cell with a perovskite film is packaged to prevent the environmental conditions from affecting its performance, and the performance is tested, including PCE, J sc , V oc and FF to evaluate the photoelectric conversion efficiency and stability of the device.
[0028] In one achievable manner, preparing a perovskite precursor solution comprises: preparing a solution containing perovskite precursor substances AX and BX2, wherein the mixed solvent system of the perovskite precursor solution is dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile; the A position is composed of any cation of cesium, rubidium, potassium, amine, amidine or alkali family, the B position is composed of any divalent metal cation of lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth and polonium; the R position is composed of any of phenylethylamine, 1,4-butanediamine and guanidine; the X position is composed of chlorine, bromine, iodine, thiocyanate, cyanide, oxycyanide, acetate, azide, borohydride, Co(CO) 4- 、C(NO2) 3- 、 C(CN) 3- The mixed solvent is DMSO, MeTHF and ACN.
[0029] The embodiment is prepared by the same process as the technical solution of the present application. The perovskite solution adopts a green solvent system, and the solvent volume ratio is adjustable. The volume ratios of DMSO: MeTHF: ACN are 1:7:2, 1:8:1, 2:7:1, 1:9:0 (verification of the necessity of ACN), 0.5:8.5:1 (fine-tuning the main solvent ratio) and 1:7.5:1.5 (further balancing volatility and solubility) multi-dimensional gradient mixed solvents. System experiments have shown that DMSO: MeTHF: ACN=1:8:1 is the optimal mixed solvent system. In addition, if the ambient humidity is disturbed, the DMSO ratio can be controlled to remain unchanged, and MeTHF: ACN can be further dynamically regulated.
[0030] The configured perovskite solution is deposited on the surface of the prepared hole transport layer ② by slit coating, wherein the coating speed of the slit coating method is 8 mm / s~50 mm / s, preferably 30 mm / s.
[0031] First, a vacuum film forming process is performed for 40 seconds, and then a thermal annealing process is performed, wherein the process temperature is preferably 150° C. and the process time is 10 minutes.
[0032] In order to illustrate the superiority of the preparation method of the perovskite photovoltaic cell of the present application, the following comparative example is now carried out: The perovskite solution configured in the comparative example adopts a conventional solvent system, the volume ratio of the solvent is adjustable, and a mixed solvent of DMF:NMP:2-Me (9:1:2) is preferably configured.
[0033] like Figure 1As shown, according to the "National Occupational Health Standard of the People's Republic of China" Occupational Exposure Limits for Hazardous Factors in the Workplace Part 1: Chemical Hazardous Factors issued by the National Health Commission of the People's Republic of China, the toxicity of DMSO, MeTHF and ACN solvents is lower than that of the commonly used perovskite preparation solvents DMF and NMP, and meets the "green" solvent standards, with no obvious toxicity and environmental burden.
[0034] like Figure 2 As shown in the figure, although DMSO and DMF have high similarity in solubility parameters, the synergistic effect of MeTHF and ACN significantly reduces the dynamic viscosity of the solution and optimizes the rheological properties of the ink, thereby improving the uniformity and controllability of the coating process. In addition, the high saturated vapor pressure characteristics of this green solvent accelerate the solvent evaporation rate, which not only increases the coating speed and enhances the production cycle, but also reduces the diffusion of perovskite colloidal particles on the substrate surface, avoiding defects such as pinholes and cracks. This improvement ensures the macroscopic uniformity and microscopic lattice consistency of the perovskite film, providing reliable technical support for the performance improvement of PV devices and their large-scale production.
[0035] During high-speed slit coating, the conventional DMF / NMP / 2-Me solvent system has a mismatch between solvent evaporation and solute deposition rates due to its lower saturated vapor pressure and higher solution viscosity. This kinetic imbalance causes the solution to flow non-uniformly on the transparent conductive substrate①, and eventually forms macroscopic defects such as ribs / stripes on the surface of the perovskite film, such as Figure 3 As shown. In contrast, the green solvent system DMSO / MeTHF / ACN of the present application has a higher saturated vapor pressure and lower viscosity, which significantly improves the solvent evaporation efficiency and reduces the surface tension of the solution. These characteristics work together to promote the uniform and orderly deposition of the solute on the substrate surface, thereby effectively avoiding the generation of the above-mentioned macroscopic defects and improving the film quality. Figure 4 The following are scanning electron microscope (SEM) images of perovskite films prepared by high-speed coating in two different solvent systems. It can be seen from the figure that when high-speed coating is applied, a large number of holes are easily generated in the conventional solvent system perovskite film, and the grains are not tightly bound, while the holes of the perovskite film in the high-volatility green solvent system of this application disappear, the grain size is larger, and the crystal quality is significantly improved. This may be due to the dynamic adjustment ability of CAN, indicating that optimizing the solvent system can improve the nucleation orientation of perovskite crystallization and obtain high-quality perovskite films with larger grain size and less defect density.
[0036] Figure 5The uniformity comparison of the perovskite film under the conditions of the conventional solvent system and the green solvent system of the present application is shown. The film is deposited at a speed of 30 mm / s on a 1200mm×650mm substrate. The perovskite film is first scribed by laser, and then the thickness of the perovskite light absorption layer is tested by a step profiler. Nine data points evenly distributed on the entire substrate are selected, where the film thickness uniformity deviation = (maximum value - minimum value) / (2*average value) * 100%. From Figure 5 It can be seen that there is an over-engraving phenomenon during the laser scribing process. By comparing the conventional solvent with the green solvent of the present application, it can be found that the perovskite film thickness curve in the comparative example fluctuates greatly, the uniformity deviation is greater than ±5%, and the overall film thickness is uneven. In the embodiment, the perovskite film under the green solvent fluctuates less, indicating that it has better film-forming properties under high-speed coating, and the film thickness deviation is only 1.73%, obtaining a more uniform perovskite film.
[0037] Table 1 Performance parameters of perovskite photovoltaic cells in two different solvent systems Figure 6 The perovskite photovoltaic cells prepared by using conventional solvents and highly volatile green solvents of the present application are JV Curve, the effective area of the module is 64.48 cm 2 , light intensity is AM1.5G 100mW / cm 2 .
[0038] Table 1 shows the performance parameters of perovskite photovoltaic cells prepared in two solvent systems. It can be seen from Table 1 that the various parameters of the perovskite photovoltaic cells prepared using the highly volatile green solvent of the present application are significantly improved, among which FF is the most significantly improved, from 69.65% to 72.99%, and PCE is increased from 14.34% to 16.51%.
[0039] It should be noted that although this application is used as an example to introduce an environmentally friendly large-area perovskite film and component preparation method as above, those skilled in the art will understand that this application should not be limited to this. In fact, users can flexibly set various parameters according to personal preferences and / or actual application scenarios, as long as the design is reasonable.
[0040] Through the technical means of the present invention, due to the DMSO: MeTHF: ACN green solvent system, the solubility and film-forming properties of perovskite are significantly improved. The coating process is further optimized by the green solvent system, which effectively reduces the use of harmful solvents in the production process and reduces the emission of toxic gases, thereby facilitating the large-scale industrial production of photovoltaic cells with perovskite thin films in the future and promoting sustainable development in this field.
[0041] The present application optimizes the solvent volatilization and film nucleation and crystallization mechanism during high-speed slit coating by carefully designing the solvent ratio combination to effectively coordinate the solubility, volatility and surface tension characteristics of the three solvents.
[0042] Specifically, DMSO as the main solvent can effectively dissolve PbI2, MAI and other precursor materials due to its strong polarity and high coordination ability. 2+ The coordination effect with the S=O group stabilizes the colloidal solution and inhibits the aggregation of colloidal particles. This improves the stability and consistency of the film. As a core green solvent, MeTHF has low toxicity (LD50>2000 mg / kg) and high volatility, which increases the upper limit of the coating rate, promotes the rapid volatilization of the solvent (the volatilization rate reaches 0.8 μL / cm²·s), reduces the residual solvent in the film, and accelerates the drying speed. At the same time, its low surface tension (28 mN / m) significantly improves the rheological properties of the solution, ensuring that the solution spreads evenly on the substrate surface, effectively avoiding coating film defects. As a dynamically controlled solvent, ACN has a high saturated vapor pressure (kPa level) and can form a complementary volatilization kinetic curve with MeTHF. In the early stage of coating (generally 0-2s), the rapid volatilization of ACN leads to a rapid decrease in the thickness of the liquid film, avoiding the coffee ring effect caused by excessive solvent retention; in the later stage of coating (2-5s), the continuous volatilization of MeTHF and the slow release effect of DMSO synergistically regulate the crystallization kinetics to obtain a dense film with a larger average grain size. This solvent system not only improves the coating process efficiency by more than 2 times through the three-stage synergistic mechanism of "strong dissolution-fast evaporation-stable crystallization", but also effectively reduces the film defect density, and at the same time reduces the solvent toxicity index (GHS classification) from Category 2 of the traditional system to Category 4, realizing the organic unity of high-performance preparation and green manufacturing. The present invention ensures the high-quality deposition of perovskite film at a high-speed coating rate of 3m / min, thereby ensuring that the device has excellent optoelectronic performance. The optimized solvent system not only breaks through the limitation of coating speed, but also improves the yield of component manufacturing. In addition, the green solvent system adopted in the present invention reduces the use of toxic solvents, reduces environmental pollution, meets environmental protection standards, and thus improves the green preparation level of PSMs. According to actual measurements, the efficiency of PSMs prepared by the solvent system of the present invention is increased from 14% to 16%, and the uniform coating of large-area (1200 mm×650 mm) films is successfully achieved, providing a feasible technical path for large-scale and efficient production. Through this technical solution, PSMs has achieved significant breakthroughs in green environmental protection, efficient production and performance improvement, and has important technical value and broad application prospects.
[0043] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a perovskite photovoltaic cell, characterized in that: The perovskite photovoltaic cell is suitable for being arranged on an external substrate, comprising the following steps: Step 1: depositing a transparent conductive substrate on a substrate, wherein the external substrate is a supporting structure of a perovskite photovoltaic cell; Step 2: preparing a hole transport layer on the transparent conductive substrate; Step 3: preparing a perovskite precursor solution using a mixed solvent of dimethyl sulfoxide, 2-methyltetrahydrofuran and acetonitrile; Step 4: coating the perovskite precursor solution on the hole transport layer to form a perovskite light absorption layer; Step 5: depositing an electron transport material on the perovskite light absorbing layer to form an electron transport layer; Step 6: preparing a hole blocking layer on the electron transport layer; Step seven: depositing a back electrode on the hole blocking layer.
2. The method for preparing a perovskite photovoltaic cell according to claim 1, characterized in that: The volume fraction of the dimethyl sulfoxide is 1% to 20%, the volume fraction of the 2-methyltetrahydrofuran is 70% to 90%, and the volume fraction of the acetonitrile is 1% to 20%.
3. The method for preparing a perovskite photovoltaic cell according to claim 2, characterized in that: The volume ratio of the dimethyl sulfoxide, the 2-methyltetrahydrofuran and the acetonitrile is 1:8:
1.
4. The method for preparing a perovskite photovoltaic cell according to claim 3, characterized in that: The dimethyl sulfoxide, the 2-methyltetrahydrofuran and the acetonitrile are fully dissolved by magnetic stirring to prepare a perovskite precursor.
5. The method for preparing a perovskite photovoltaic cell according to claim 4, characterized in that: The perovskite precursor solution was deposited on the hole transport layer by slot coating and annealed at 150° C. for 10 min.
6. The method for preparing a perovskite photovoltaic cell according to claim 5, characterized in that: The substrate is a glass substrate, and one of an indium tin oxide thin film and a fluorine-doped tin oxide thin film is deposited on the glass substrate to form a transparent conductive substrate; A nickel oxide film is deposited on the conductive substrate by spin coating or magnetron sputtering to form the hole transport layer.
7. The method for preparing a perovskite photovoltaic cell according to claim 6, characterized in that: A fullerene layer is deposited on the perovskite active layer by thermal evaporation or spin coating to form the electron transport layer.
8. The method for preparing a perovskite photovoltaic cell according to claim 7, characterized in that: A bath copper layer is deposited on the electron transport layer by thermal evaporation or spin coating to form the electron transport layer.
9. The method for preparing a perovskite photovoltaic cell according to claim 8, characterized in that: A bath copper layer is deposited on the electron transport layer by thermal evaporation or spin coating to form the hole blocking layer.
10. The method for preparing a perovskite photovoltaic cell according to claim 9, characterized in that: A metal electrode is deposited on the hole blocking layer to form the back electrode, and the back electrode is made of silver or copper.
Citation Information
Patent Citations
Solvent system for preparing perovskite thin film through solution method and application of solvent system
CN117651463A
High-volatility solvent system used in perovskite solar cell
CN117794339A
Low-boiling-point ink, method for preparing perovskite thin film from low-boiling-point ink and photovoltaic application of low-boiling-point ink
CN118307990A
Recycling method of perovskite solar cell module and perovskite solar cell manufactured by the method
KR102670841B1
Cited By
Perovskite cell with low-temperature evaporation antireflection film and preparation method thereof
CN120936174A